2014
DOI: 10.3892/br.2014.405
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neural stem cells and bone marrow derived-mesenchymal stem cells during differentiation

Abstract: Due to their capacity to self-replicate or produce specific differentiated cell types, neural stem cells (NSCs) and bone marrow derived-mesenchymal stem cells (BMSCs) are potential sources for cell transplantation therapies, particularly for neural injury. However, the interaction between NSCs and BMSCs during differentiation has not yet been defined. The interaction is believed to improve the effectiveness and efficiency of cell therapy. In the present study, human NSCs and BMSCs were cultured and the Transwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…NSCs are known to secrete growth factors like BDNF and FGF stimulating WJ-MSC differentiation into the neural direction. Our observation is coherent with Rong’s group [ 31 ], where the authors concluded that NSCs promoted BM-MSCs to differentiate into neuronal direction, the most probably via BDNF and NGF stimulatory interaction. Similar interplay was also described by Salgado [ 32 ], who underlined the importance of paracrine interactions between hMSCs and NSCs in the stimulated neurogenic niches.…”
Section: Discussionsupporting
confidence: 92%
“…NSCs are known to secrete growth factors like BDNF and FGF stimulating WJ-MSC differentiation into the neural direction. Our observation is coherent with Rong’s group [ 31 ], where the authors concluded that NSCs promoted BM-MSCs to differentiate into neuronal direction, the most probably via BDNF and NGF stimulatory interaction. Similar interplay was also described by Salgado [ 32 ], who underlined the importance of paracrine interactions between hMSCs and NSCs in the stimulated neurogenic niches.…”
Section: Discussionsupporting
confidence: 92%
“…40 cases per million individuals are diagnosed as SCI [ 3 ]. Bone marrow-derived mesenchymal stem cells (BMSCs), which possess immunosuppressive properties and the capacity for unlimited self-amplification and for terminal differentiation [ 4 , 5 ], play a privileged role in ameliorating neuronal damage in CNS disease models including SCI [ 6 ]. Cellular replacement with MSCs in different SCI animal models has showed functional recovery [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated the ability of MSCs to secrete EVs containing multiple miRNAs that can be transferred to cells, and miR-223 is highly expressed in BMSCs [ 25 ]. Notably, interaction between BMSCs and NSCs has been documented to fundamentally exercise the simulative effects on differentiation of BMSCs into NSCs and neuron cells [ 26 ]. Additionally, miR-133b has been proven to be delivered to the neurons via EVs secreted from MSCs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%